CNS Langerhans cell histiocytosis: Common hematopoietic origin for LCH‐associated neurodegeneration and mass lesions. Issue 12 (6th April 2018) - McClain, Kenneth L.; Picarsic, Jennifer; Chakraborty, Rikhia; Zinn, Daniel; Lin, Howard; Abhyankar, Harshal; Scull, Brooks; Shih, Albert; Lim, Karen Phaik Har; Eckstein, Olive; Lubega, Joseph; Peters, Tricia L.; et al.
Abstract : BACKGROUND: Central nervous system Langerhans cell histiocytosis (CNS‐LCH) brain involvement may include mass lesions and/or a neurodegenerative disease (LCH‐ND) of unknown etiology. The goal of this study was to define the mechanisms of pathogenesis that drive CNS‐LCH. METHODS: Cerebrospinal fluid (CSF) biomarkers including CSF proteins and extracellular BRAF V600E DNA were analyzed in CSF from patients with CNS‐LCH lesions compared with patients with brain tumors and other neurodegenerative conditions. Additionally, the presence of BRAF V600E was tested in peripheral mononuclear blood cells (PBMCs) as well as brain biopsies from LCH‐ND patients, and the response to BRAF‐V600E inhibitor was evaluated in 4 patients with progressive disease. RESULTS: Osteopontin was the only consistently elevated CSF protein in patients with CNS‐LCH compared with patients with other brain pathologies. BRAF V600E DNA was detected in CSF of only 2/20 (10%) cases, both with LCH‐ND and active lesions outside the CNS. However, BRAF V600E + PBMCs were detected with significantly higher frequency at all stages of therapy in LCH patients who developed LCH‐ND. Brain biopsies of patients with LCH‐ND demonstrated diffuse perivascular infiltration by BRAF V600E + cells with monocyte phenotype (CD14 + CD33 + CD163 + P2RY12 ‐ ) and associated osteopontin expression. Three of 4 patients with LCH‐ND treated with BRAF‐V600E inhibitor experienced significant clinical and radiologic improvement. CONCLUSION: In LCH‐ND patients, BRAF V600E + cells in PBMCs and infiltrating myeloid/monocytic cells in the brain is consistent with LCH‐ND as an active demyelinating process arising from a mutated hematopoietic precursor from which LCH lesion CD207 + cells are also derived. Therapy directed against myeloid precursors with activated MAPK signaling may be effective for LCH‐ND. Cancer 2018;124:2607‐20 . © 2018 American Cancer Society . Abstract : While LCH‐associated neurodegeneration (LCH‐ND) has historically been considered to be an autoimmune or paraneoplastic phenomenon, identification of BRAF V600E + myelo‐monocytic cells in peripheral blood and at sites of neurodegeneration is more consistent with a hematopoietic origin of LCH‐ND. A pathogenic role for these infiltrating BRAF V600E + cells is supported by clinical and radiological responses of patients with LCH‐ND to BRAF‐V600E inhibition.